Ca2+, annexins, and GTP modulate exocytosis from maize root cap protoplasts - Carroll, AD (1998)
Protoplasts isolated from root cap cells of maize were shown to secrete fucose-rich polysaccharides and were used in a patch-clamp study to monitor changes in whole-cell capacitance. Ca2+ was required for exocytosis, which was measured as an increase in cell capacitance during intracellular dialysis with Ca2+ buffers via the patch pipette. Exocytosis was stimulated significantly by small increases above normal resting [Ca2+]. In the absence of Ca2+, protoplasts decreased in size. In situ hybridization showed significant expression of the maize annexin p35 in root cap cells, differ-entiating vascular tissue, and elongating cells. Dialysis of protoplasts with maize annexins stimulated exocytosis at physiological [Ca2+], and this could be blocked by dialysis with antibodies specific to maize annexins. Dialysis with milli-molar concentrations of GTP strongly inhibited exocytosis, causing protoplasts to decrease in size. GTPgammaS and GDPbetaS both caused only a slight inhibition of exocytosis at physiological Ca2+. Protoplasts were shown to internalize plasma membrane actively. The results are discussed in relation to the regulation of exocytosis in what is usually considered to be a constitutively secreting system; they provide direct evidence for a role of annexins in exocytosis in plant cells.